2010
DOI: 10.1016/j.eurpsy.2010.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Association between cingulum bundle structure and cognitive performance: An observational study in major depression

Abstract: Brain structural tissue markers of the middle-anterior and middle-posterior cingulum bundle were found to be associated with executive functioning and divided attention in patients with major depression. Disconnection within the limbic-cortical networks may underlay cognitive dysfunction in major depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 36 publications
3
43
0
Order By: Relevance
“…24 Besides the association of the cingulate cortices, cingulum fibers connect the middorsolateral frontal cortex with retrosplenial and parietal cortices, thalamus, hippocampus, and parahippocampal gyrus, and they have been suggested to be involved in executive functioning. 25 With respect to memory performance, the association between verbal learning and memory test scores and fornix MD and FA values is well established and has been documented in DT MR imaging studies of patients with other neurodegenerative and psychiatric diseases. 26,27 On the contrary, the relationship between visuospatial abilities and left uncinate FA is unexpected and should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 97%
“…24 Besides the association of the cingulate cortices, cingulum fibers connect the middorsolateral frontal cortex with retrosplenial and parietal cortices, thalamus, hippocampus, and parahippocampal gyrus, and they have been suggested to be involved in executive functioning. 25 With respect to memory performance, the association between verbal learning and memory test scores and fornix MD and FA values is well established and has been documented in DT MR imaging studies of patients with other neurodegenerative and psychiatric diseases. 26,27 On the contrary, the relationship between visuospatial abilities and left uncinate FA is unexpected and should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous cognitive processes that engage the hippocampus and ACC may be affected by compromised PC integrity. Earlier studies have shown that PC integrity corresponds significantly with verbal (Delano-Wood et al, 2012) and visual memory abilities (Kantarci et al, 2011), as well as executive processes (Schermuly et al, 2010) such as the suppression of pre-potent response, as required by the Stroop task (Metzler-Baddeley et al, 2012). Notably, impairments in these processes characterize anxious individuals (Bremner et al, 2004;Gilbertson et al, 2001;Vasterling et al, 1998;Vasterling et al, 2002;Yehuda et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Disruptions in this region are likely to adversely influence both affective and cognitive processes. Regarding cognition, degraded PC microarchitecture has been linked to Alzheimer's disease (Zhang et al, 2007), mild cognitive impairment (Delano-Wood et al, 2012;Drago et al, 2011), and poorer performance on measures of selective attention, executive function (Schermuly et al, 2010), and memory (delayed recall; Kantarci et al, 2011), illustrating the salience of PC integrity in higher-order executive processes. Taken together, these findings suggest that PC disruptions have consequences for processing of incoming emotional and cognitive information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hippocampal dysfunction and atrophy associates with mood disorders (Small et al, 2011), and in normal and neurodegenerative conditions, DTI measures of WM microstrucure of the hippocampal part of the cingulum bundle correlate with memory scores and hippocampal volume (Sexton et al, 2010). The cingulum bundle integrates disparate modular brain systems involved in attention, memory, and emotion regulation, and in mood disorders, a higher directionality of water diffusion in the cingulum bundle associates with better hedonic tone (Keedwell et al, 2012), better cognitive performance (Schermuly et al, 2010), and less psychomotor slowing (Walther et al, 2012). The number of fibers within the uncinate fasciculus inversely correlated with depression severity (Zhang et al, 2012).…”
Section: Lithium and Gsk3-b Effects On White Matter F Benedetti Et Almentioning
confidence: 99%